Pengabdian Masyarakat: Gerakan Buang Sampah Pada Tempatnya Dan Penerapan 3r Sebagai Upaya Pelestarian Tanah Dan Lingkungan Di Desa Selli Kec. Bengo Kab. Bone - Nur Adila Syahid; Andi trisnowali MS; Wahyuningsih, Wahyuningsih; Khahfi, Muh. Ash Habul Thoriq; Egidia, Rhegita; Nurfadilah, Nurfadilah; Rahman, Nurazisah; Nislawati, Nislawati; Wahyuni, Nurul; Lukman, Lukman; Risaldi, Risaldi (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The waste problem remains a major challenge in maintaining environmental sustainability, particularlyrelated to soil quality. People's habit of littering causes pollution, reduces soil fertility, and has negativeimpacts on health. Through this community service activity, efforts were made to raise public awarenessabout the importance of disposing of waste properly and introduce the 3R concept (Reduce, Reuse, Recycle) asa method of sustainable waste management. The activity was carried out through socialization and directpractice with the community of Selli Village, Bengo District. The socialization included an explanation of theimpact of waste on the environment, while the direct practice included waste sorting, making simple compost,and reusing used goods that can still be used. The results of the activity showed an increase in communityunderstanding of the dangers of waste if not managed properly. In addition, a shared commitment wasformed to get used to disposing of waste properly and applying the 3R principle in everyday life. Thecommunity also began to be able to utilize organic and inorganic waste more productively. This communityservice activity is effective in fostering a culture of environmental awareness while also being a concrete stepin preserving the soil and creating a cleaner and more sustainable environment.